The Effect of Force Ratio Multiplier on A Control System for Surfing Problem Simulation - Reza Rendian Septiawan; Agus Virgono; Umar Ali Ahmad; Prayitno Abadi; Mas'ud Adhi Saputra (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2022)
A surfing problem is a control problem of the surfing board to maintain its position on top of an ocean wave as long as possible. There are some physical and mathematical problems regarding a surfing problem that have not yet been solved. One of them is on translating a target inclination problem from an ordinary differential equation (ODE) control system to the inclination control system via the distribution of a surfer’s weight. To move the surfing board swiftly, a correct value of the multiplier, which is notated by σ, is needed on the weight distribution system. In this work, an investigation has been done on the effect of the multiplier in an attempt to help moves the surfing board fulfils the target inclination angle needed by using a smoothed particle hydrodynamics (SPH) simulation. The result from this work shows that the best value for the multiplier is σ=10 that gives the smallest average positional error for some variations of a given target position. This work gives a contribution on an attempt to model a surfer’s phenomenon mathematically.